Carcass Quality and Tetracycline Residues in Broiler Chicken Meat in Banyuwangi Traditional Market - Subagyo, Safira Fauziyyah; Harijani, Nenny; Wibawati, Prima Ayu; Effendi, Mustofa Helmi; Chusniati, Sri; Yunita, Maya Nurwartanti (Universitas Airlangga, 2021)
This study aimed to examine the quality of broiler carcasses in the Banyuwangi traditional market with carcass quality examination based on SNI number 3924-2009 and tetracycline antibiotic residues test based on SNI number 7424:2008. A total of ten broiler chicken sellers as representative of almost all broiler chicken sellers in the Banyuwangi market, with each seller was taken for one carcass in this research. Carcass quality examination used a standart carcasses weight 1,0-1,3 kg. Carcass quality examination was carried out with descriptive analysis with reference to the physical characteristics of SNI (Standarisasi Nasional Indonesia). The bioassay method is used to test for tetracycline antibiotic residue. The result of the carcass quality examination showed that from the whole sample consisting of conformation, disjointed or broken bones and missing parts, discolorations, and cleanliness of broiler carcasses are good enough. The percentage quality of broiler carcasses quality I is 60%, quality II is 30% and quality III is 10%. The examination of antibiotic tetracycline residues in broiler meat showed negative results indicating that no feeds containing additional antibiotics made carcasses in the traditional Banyuwangi market safe for consumption.